Adaptation and Validation of the Vietnamese-Translated Diabetes Knowledge Questionnaire - Nguyen, Thao; Tran, Tam; Diep, Han; Vo, Son; Taxis, Katja; Nguyen, Thang (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objectives. There is no existing Vietnamese diabetes knowledge questionnaire. This impedes assessment of patient knowledge that will be helpful in providing effective diabetes intervention. We aimed to validate the Vietnamese-translated Diabetes Knowledge Questionnaire (DKQ). Methodology. Translation and adaptation strictly followed the guidelines of Beaton et al. Internal consistency was assessed by Cronbach’s alpha coefficient, test-retest reliability was assessed by Fleiss’ Kappa coefficient, and validity value was determined among type 2 diabetes patients in a general hospital. Results. The Vietnamese version of the DKQ had good internal consistency (Cronbach’s alpha for all items = 0.898) and stability (Kappa coefficient >0.600). The average score for all equivalence criteria was 1.00, demonstrating good equivalence to the original. The significant difference between knowledge score and education level (p <0.001) confirmed construct validity. Conclusion. Our study provided a reliable Vietnamese version of the DKQ. Future studies may apply the version in different regions in Vietnam to determine external validity.